Watson-Crick petri net languages: the effect of labeling strategies - Mohamad Jan, Nurhidaya; Fong, Wan Heng; Sarmin, Nor Haniza; Turaev, Sherzod (American Institute of Physics, 2014)
A Watson-Crick automaton is an automaton that works on tapes which are double stranded sequences of symbols related by Watson-Crick complementarity that are similar to the DNA molecules. However, this automaton cannot exploit the other fundamental features of DNA molecules such as the massive parallelism. Watson-Crick automata can be related to a model known as the Petri net. Petri net is a model based on the concepts of asynchronous and concurrent operation by the parts of a system and the realization by the parts can be represented by a graph or a net. From the relation between Watson-Crick automata and Petri net, a new model namely Watson-Crick Petri net has been developed. The language generated by Watson-Crick Petri net is a set of labeled sequences corresponding to the occurrence sequences of the model. In this research, some properties of languages generated by Watson-Crick Petri net are investigated.